Quantitative analysis of three-dimensional choroidal changes in coronary artery disease patients with swept-source optical coherence tomography angiography - Zhaoxia Zheng; Jing Liu; Jiayi Sun; Yue Zhang; Xiaoya Gu; Shuang Song; Xiaobing Yu (Photodiagnosis and Photodynamic Therapy)
Purpose: To quantitatively analyze three-dimensional (3D) choroidal changes in coronary artery disease (CAD) patients with swept-source optical coherence tomography angiography (SS-OCTA) based on a scan area of 12×12mm. Methods: 236 CAD patients and 78 controls were included after coronary angiography (CAG) evaluation in this prospective cross-sectional study. Choroidal and foveal avascular zone (FAZ) parameters were compared between the two groups. Choroidal morphological characteristics were also evaluated based on ETDRS quadrants. Receiver operating characteristics (ROC) curves were generated to determine the discriminative power of choroidal and FAZ parameters. Linear regression analysis was used to determine the relationships between Gensini score and choroidal parameters. Results: Choroidal thickness (CT), choroidal vascular volume/ area (CVV/a), and choroidal stromal volume/ area (CSV/a) were significantly reduced in CAD patients, while 2D vascular density decreased only in 1–6 mm, and no statistical difference in choroidal vascularity index (CVI) values was detected. The AUC values of choroidal parameters were greater in the inner-6 mm area than the outer-6 mm area, and good performance was found with a combination with FAZ parameters (AUC=0.77, P < 0.001). For morphological analysis, both groups showed the greatest values in superior quadrant and the lowest in nasal quadrant. After controlling for confounding factors, Gensini score was negatively associated with CT (β = -0.35, P = 0.003), CVV/a (β = -0.17, P = 0.004), and CSV/a (β = -0.18, P = 0.005). Conclusion: The SS-OCTA provided excellent visualization and quantification of the choroid and showed decreased choroidal thickness and volume in CAD patients, but the morphological features were unchanged. The severity of coronary artery stenosis was independently associated with choroidal changes.